A cell attracting composite of lumbar fusion cage. Issue 8 (24th May 2017) - Gunay, Busra; Hasirci, Nesrin; Hasirci, Vasif
Abstract: Lumbar fusion cages are devices used in spinal fusion procedures for disorders such as spondylosis and degenerative disc diseases that may occur due to age, trauma or genetic reasons. These devices are most frequently made of metals and polymers. The mechanical properties of such devices should be comparable to the bone to avoid stress shielding. Besides, cages should interact with the cells to prevent extrusion and achieve satisfactory fusion. In this study, poly(methylmethacrylate) (PMMA) and hydroxyapatite (HAp) were compounded to create products with HAp contents up to 40% (w/w), processed by hot melt extrusion and injection molded to produce composites with maximum polymer-mineral interaction. The morphology, interaction with the plates and rate of proliferation of human osteoblast-like (HOB) cells were studied in vitro . We learned that cells interact more with HAp when the HAp content is higher than 20%. Tensile and compressive properties of PMMA were significantly increased with increasing HAp content; from an elastic modulus ( E ) of 2.08 to 3.92 GPa in tension, and from 349 to 562 MPa in compression. High HAp content of the samples increased the roughness from 0.69 μm for pure PMMA to 1.35 μm for 40% (w/w) HAp loaded PMMA, increased cell proliferation and as a result the cells presented filopodia indicating a satisfactory level of interaction with the cage surface. Based on mechanical and in vitro studies, a HAp content of around 30% (w/w) was found to be appropriate for good cell adhesion and satisfactory mechanical properties for use in the construction of a fusion cage. It was concluded that when PMMA and HAp were compounded at an optimal value, a cage material with adequate mechanical properties and increased cell attachment can be obtained for use in spinal fusion applications.